TUMOR OF THE LOWER JAW IN PEDIATRIC PATIENT WITH DEVELOPMENTAL DELAY: A CASE REPORT AND LITERATURE REVIEW - Elissa Chairani; Aris Setyawan; Audrey Anggun Unique; Dedy Agoes Mahendra; Fitra Nabiila Alfiona; Raudin Novia Ghazani (Jurnal Kedokteran Diponegoro, 2025)
Background: Ossifying fibroma (OF) is a benign bone neoplasm that mostly appears in the jaw. OF generally occurs between the second and fourth decades of life. OF can be challenging for clinicians, especially if the patient is in a vulnerable state. This case is particularly significant as it presents OF in a pediatric patient with developmental delay, which can complicate the diagnostic process and affect the accuracy of the patient's complaints. Purpose: This article presents a pediatric patient with developmental delay, which shows evidence of a jaw tumour. Case: A 12-year-old male patient with a chief complaint of swelling that gradually increased in size on the left lower jaw three months ago reported to the Department of Oral and Maxillofacial Surgery Mardi Rahayu Hospital Kudus and later on was diagnosed with OF. This case presents the management of OF in a patient with a particular condition of developmental delay, specifically in socioemotional delay. Case Management: Management of OF may need comprehensive treatment, including pre-operative preparation, supporting examination through radiographic and microscopic imaging, consideration of excision technique, and post-surgery follow-up. Conclusion: The unique challenges presented by the patient's developmental delay highlight the need for careful and clear communication of the treatment plan to ensure a good prognosis.